DETECTION OF HUMAN HERPESVIRUS-8 ANTIGEN IN HIV-INFECTED PATIENTS IN EAST JAVA, INDONESIA - Oktafiani, Devi; Megasari, Ni Luh Ayu; Fitriana, Elsa; Nasronudin, Nasronudin; Lusida, Maria Inge; Soetjipto, Soetjipto (African Journal of Infectious Diseases (AJID), 2018)
Background: Co-infection of human herpesvirus-8 (HHV-8) in HIV-positive people might cause Kaposi's sarcoma. Earlydetection of HHV-8 may prevent the onset of clinical manifestations. In Indonesia, detection of HHV-8 antigen in HIVpositivepatients has yet to be reported. The intention of this research was to examine the presence of HHV-8 antigen inHIV-positive patients in East Java, Indonesia.Material and Methods: 103 serum samples were collected from HIV-positive patients in Surabaya and Tulungagung, EastJava, Indonesia. Serums were then tested for the presence of HHV-8 antigen by using sandwich ELISA.Results: Human Herpesvirus-8 antigen was detected in 15 samples (14.5%). The presence of HHV-8 infection in HIVpositivepatients did not present differently in males and females and among different age groups. Humanimmunodeficiency virus-positive serum samples were collected from 23 homosexual men, 25 intravenous drug users(IVDUs) and 52 heterosexuals. In the male homosexual group, HHV-8 antigen was detected in 21.7% (5/23) of thesamples, while in the intravenous drug user group (IVDUs), 16% (4/25) of the samples were found to have HHV-8 antigen.Conclusion: This research found the presence of HHV-8 antigen in 14.5% of patients in East Java, Indonesia. It isrecommended that patients with a positive result should receive further examination to detect any clinical manifestationsrelated to HHV-8 infection, especially in the form of Kaposi’s sarcoma lesions, so that the illness can be appropriatelymanaged.